Road to ruin - Laurance, William (Himalayan Journal of Sciences, 2008)
Tough laws won’t save poor nation’s ecosystems until the impacts of developments are taken seriously Reprinted with permission from New Scientist, issue 2607, 06 June 2007, page 25 Himalayan Journal of Sciences Vol.4(6) 2007 p.9